Challenging conventional wisdom: Experimental evidence on heterogeneity and coordination in avoiding a collective catastrophic event - Israel Waichman; Tilman Requate; Markus Karde; Manfred Milinski (Kiel Centre for Globalization (KCG), 2019)
Avoiding a catastrophic climate change event is a global public good characterized by several dimensions, notably heterogeneity between the parties involved. It is often argued that such heterogeneity between countries is a major obstacle to cooperative climate policy. We challenge this belief by experimentally simulating two important heterogeneities, in wealth and loss, when dangerous climate change occurs. We find that under loss heterogeneity the success rate in achieving sufficient mitigation to prevent catastrophic climate change is higher than with homogeneous parties. We also observe that neither endowment heterogeneity nor the combination of endowment and loss heterogeneities lead to significantly different success rates than with homogeneous parties. Our findings suggest that heterogeneities may facilitate rather than hinder successful international climate policy negotiations.
Keywords: C92; D74; H41; Q54; 330; global public good; change negotiation; collective-risk social dilemma; endowmentheterogeneity; loss heterogeneity; focal point